Ukraine as a Country of Focus for the Government of Canada in the Context of Russia’s Aggression - Валентин Балюк (Історико-політичні проблеми сучасного світу)
The central thesis of this paper is that Canadian-Ukrainian relations have fostered certain peculiarities due to the fact that in Canada (the Land of Maple Leaf), a hefty percentage of citizens are of the Ukrainian origin. Social mobility of the Canadian Ukrainians is traditionally forcing top-level authorities to have their focus resolve around the Ukrainians’ needs and expectations. Noteworthy, since the World War II, Canada has been a pivotal role in constant efforts to strengthen Ukraine’s democracy. While ardently supporting Ukraine’s will for gaining its independence, after dissolution of the Soviet Union, Canada’s government acted in compliance with the international law. Particularly, the Soviet Union’s collapse put Ukraine on the map of the international political landscape and made it known to become independent from the Russian Federation. It should be articulated, Poland was first country to recognize the independence of Ukraine on December 2, 1991. Canada was the second world state to have acknowledged Ukraine to be a sovereign state. In the 30-year-long-run Ukraine gained worldwide recognition. Undoubtedly, Ukraine- Canada relationship has laid its crucial fundamentals for the global acknowledgment. The author of the article estimates that both countries have signed more than 50 documents, which are handling their relationship. According to the author, sovereign Ukraine is an especially important factor for European security, which is facilitated by the present-day Canada-Ukraine relations. The author of the article emphasizes on Canada-Ukraine relations to be recognized as a unique and genuine partnership. To be more precise, the scholar discloses the significant value of the Joint Declaration on Special Partnership signed in 1994, which was extended twice - in 2001 and 2008. Remarkably, the paper analyzes Canadian-Ukrainian relations from the beginning till 2018. It highlights two stages f the relations establishment - before 2014 and after the Russia’s aggression against Ukraine. Furthermore, the author stresses on his personal contribution in the scientific research on Canada’s policy in terms of Russia’s aggression against Ukraine over the years. Provisions of the article are proved by the relevant Canadian-Ukrainian documents. In addition to the mentioned Declaration, there is an Agreement on Friendship and Cooperation between Ukraine and Canada, dated 1994. Document reaffirmed both sides’ commitment to the democratic values and the principles of market economy. It also defined development in the political, security, economic, social and cultural areas of Ukraine-Canada relations. Since the article is devoted to bilateral relations between the two countries in extremely difficult time for Ukraine, related to Russian aggression, article says a lot about the aggression itself, about the support for Ukraine to overcome it, about the reaction of the world society. To confirm it, author involved a bilateral document Defence Cooperation Arrangement, dated April 3, 2017. The body of the article goes on to emphasize Canada’s bolstering democratic and market reforms in Ukraine. However, the author draws attention that the current trade and mutual investments capacity leaves much to be desired. Nevertheless, the Canada government and the pro-Ukrainian Canadians provided significant support to Ukraine during the Orange Revolution and the Revolution of Dignity. Authorities in Ottawa denounced Russia’s aggression against Ukraine by joining the sanctions imposing policy of the Western countries. Ottawa has clearly spoken out against Russia’s annexation of Crimea and destabilization in Donbas and supported sale of the lethal weapons to Ukraine. First of all, Canada supports Ukraine through diplomatic policy, as well as in Ukraine’s efforts in implementing economic reforms and strengthening the state security system.